Nepali Paintings: A Departure From Religious Contents to Secular Subject Matters - Sharma, Yam Prasad (Tribhuvan University Journal, 2021)
Traditional Nepali paintings are religious since they are based on Hindu and Buddhist myths. Manuscript illuminations and paubhas, the examples of religious paintings, have magical and mystical contents. Characters of myths have been portrayed and mythical stories have been narrated in visual form. There are a series of changes from traditional Nepali paintings to contemporary works. In painting, secular elements are introduced through didactic visual narratives from Hitopadesha manuscript. The moral lessons are taught through animal fables. Early paubhas are fully religious but later paubhas include portraits of the donors or the persons who asked to paint the picture at the bottom of the painting. The main part of the painting is religious but the portraits are secular. In later paubhas, the figures of the donors become larger and take equal space in the painting. Gradually, the portrait became bigger than the religious figure at the end of the Malla period. From the beginning of the Shaha period, portraits existed independently. During the Rana rule, the art of portrait painting reaches the climax since the Ranas loved the image of themselves and their family members. The artworks exist independently without reference to myths and religious texts. There is the transition from religious contents to secular subject matters. This article traces the development of secular elements in Nepali paintings. It compares the paintings in terms of the inclusion of secular elements.